2020
DOI: 10.3390/foods9020244
|View full text |Cite
|
Sign up to set email alerts
|

Use of Phycobiliproteins from Atacama Cyanobacteria as Food Colorants in a Dairy Beverage Prototype

Abstract: The interest of the food industry in replacing artificial dyes with natural pigments has grown recently. Cyanobacterial phycobiliproteins (PBPs), phycoerythrin (PE) and phycocyanin (PC), are colored water-soluble proteins that are used as natural pigments. Additionally, red PE and blue PC have antioxidant capabilities. We have formulated a new food prototype based on PBP-fortified skim milk. PBPs from Andean cyanobacteria were purified by ammonium sulfate precipitation, ion-exchange chromatography, and freeze-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…Other studies have reported the incorporation of PE in food products (Galetovic et al., 2020; Jayasinghe et al., 2016; Sudhakar et al., 2014, 2015) but, to the best of our knowledge, there are no reports in the incorporation of PE in bakery products. Jayasinghe et al.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Other studies have reported the incorporation of PE in food products (Galetovic et al., 2020; Jayasinghe et al., 2016; Sudhakar et al., 2014, 2015) but, to the best of our knowledge, there are no reports in the incorporation of PE in bakery products. Jayasinghe et al.…”
Section: Resultsmentioning
confidence: 86%
“…PBPs have been used in food by incorporation in gelatin desserts, puddings, sourdough, and soft and dairy beverages, though its use needs to be further supported by toxicity testing (Chentir et al., 2019; Galetovic et al., 2020; Jayasinghe, Pahalawattaarachchi, & Ranaweera, 2016; Niccolai et al., 2019; Sudhakar, Jagatheesan, Perumal, & Arunkumar, 2015; Sudhakar, Saraswathi, & Nair, 2014). While in Europe there is no authorization for the use of PE as a food colorant or additive, in France and Asia C‐PCs extracted from Spirulina are authorized in foods such as ice creams, candies, and drinks (Dumay & Morançais, 2016; Fleurence, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Another prominent colourant from the microalgae with commercial applications is phycobiliproteins, a water-soluble fluorescent pigment commonly present in cyanobacteria which can be classified as four major groups according to their colours and light absorption characteristics, namely, phycoerythrin, phycocyanin, allophycocyanin and phycoerythrocyanin [129,130]. The phycobiliproteins were shown as a strong antioxidant which contributes to high-value nutraceutical product and its application in food mainly in dairy products, chewing gums, candy, beverage mixes and ready-to-eat cereals [131,132]. Besides being a functional ingredient and safe food colourant, this protein (eg.…”
Section: Natural Pigmentsmentioning
confidence: 99%
“…Phycobiliproteins have been incorporated in desserts, puddings, sourdough, soft drinks, and dairy products, although their use needs to be further supported by toxicity testing. Moreover, additional research focusing on bioavailability and on the interaction of phycobiliproteins with food, beverages, matrixes, and stabilizers among others is required [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%